1-Ethyl-3-methylimidazolium tetrafluoroborate-doped high ionic conductivity gel electrolytes with reduced anodic reaction potentials for electrochromic devices. (15th March 2017) - Tang, Quanfeng; Li, Haizeng; Yue, Yanfang; Zhang, Qinghong; Wang, Hongzhi; Li, Yaogang; Chen, Pei
Abstract: The electrolyte plays an important role in an electrochromic device (ECD), and an ideal electrolyte can greatly improve the electrochromic performance of the device. Here, we report the preparation of a 1-Ethyl-3-methylimidazolium tetrafluoroborate ([Emim]BF4 )-doped Poly(methyl methacrylate) (PMMA)-based gel electrolyte for electrochromic applications. By the doping of the [Emim]BF4, the ionic conductivity of the gel electrolyte is improved (2.9 × 10 − 3  S/cm at room temperature and 10 − 2  S/cm at 40 °C). Most importantly, the addition of the [Emim]BF4 could reduce the anodic reaction potentials in an ECD, which could enable ECD bleaching at smaller applied voltages and avoid the degradation of optical modulation induced by ion-trapping in tungsten oxide (WO3 ) films. This novel electrolyte provides a promising platform for low anodic reaction potential electrochromic devices. Graphical abstract: Highlights: The gel electrolyte with reduced anodic reaction potential was introduced in electrochromic devices. The gel electrolyte exhibits high ionic conductivity due to the addition of charge carriers from ionic liquid. Electrochromic devices assembled with the gel electrolyte exhibit higher contrast under small applied potentials.